Peran Reputasi Perusahaan dalam Memediasi Pengaruh Corporate Social Responsibility dan Ukuran Dewan Direksi terhadap Kinerja Keuangan Perusahaan - Adelina Citradewi; Evi Widiani (Universitas Negeri Padang, 2024)
In the last five years, service industry companies have experienced the sharpest decline in financial performance compared to companies in other sectors. This research aims to determine the effect of CSR and the size of the board of directors on financial performance, which is mediated by company reputation. The population used in this research is all service industry issuers registered on the IDX (Indonesian Stock Exchange), totaling 1,338 issuers in 2019-2021. Purposive sampling is the technique of choice in sampling decisions, and a total sample of 69 issuers was obtained. The data analysis techniques used in this research are panel data regression analysis and path analysis. Based on the research results, it was concluded that the CSR variable had an effect on the company's reputation, the company's reputation had an effect on the company's financial performance, the size of the board of directors had no effect on the company's reputation, CSR and the size of the board of directors had no effect on the company's financial performance and could not be mediated by the company's reputation. Future research can expand the research sample and variables so that the coverage is broader and more factors can influence the company's financial performance.